New mathematical modelling for grain size distribution adjustment in concrete - Cruz, C. M.; Morais, E. M. [UNESP]; Grillo, R. H.F.; Roveri, C. D.; Maestrelli, S. C. (FapUNIFESP (SciELO), 2019)
Concrete used in civil engineering is a composite obtained from the combination of coarse and fine aggregates, cement and water, and its cost and quality are normally associated to the proportion of its constituents (ceramic formulation), as well as the reduction of water consumption. The aggregates used in concrete may have diverse origins, and the syenite extracted at Pedra Branca Alkaline Massif is one of the materials that can be used for this substitution. In order to do so, a reference formulation of concrete was calculated and optimized using the mathematical models of Andreasen, and syenite was added substituting 25, 50, 75 and 100% of the fine aggregate. In order to maintain the original granulometric distribution, an algorithm was developed to compensate the different particle size distributions. The grain size correction guaranteed the maintenance of the original properties of the concrete, reaching values of mechanical strength above 35 MPa.
Keywords: Algorithm; Concrete; Mechanical properties; Packing equations; Syenite